Design of a new film with predefined properties based on chitosan - Dubinina, Antonina; Zaytseva, Valentyna; Lehnert, Svitlana; Vindyk, Andriy; Cherevko, Oleksander; Tatar, Larysa; Skyrda, Olena; Prasol, Svitlana (Eastern-European Journal of Enterprise Technologies, 2024)
Synthetic and chitosan-based polymer films were selected as the object of this study. Chitosan is a natural non-toxic oligosaccharide of animal origin capable of biological destruction. The task addressed in this work is to design a chitosan-based film with increased bacteriostatic properties for use in combined packaging material as a protective layer. The use of such films would provide for the biodegradability of packaging materials, which could make it possible to reduce the use of synthetic polymers in packaging and improve the environment. A feature of the proposed method is that a decoction of yarrow grass is used as a chitosan solvent, which leads to the acquisition of bacteriostatic properties by the films. It has been established that the highest bacteriostatic effect is achieved in this case. The results of the research showed a significant growth retardation zone of E. coli, B. cereus, B. subtilis, P. aeruginosa, S. aureus, C. albicans, Saccharomyces and Lactobacillus strains. The set of studies made it possible to optimize the recipe composition of films based on chitosan (%): chitosan – 2.0...2.5, glycerin – 1.0...1.5, decoction of yarrow grass – 96...97 (according to the ratio of medicinal plant raw materials:water – 1:10). It was determined that the values of indicators of the destructive stress at the rupture of the designed films (14.0...16.0 MPa) exceed the permissible minimum, which should be 13.7 MPa for polymer films. The designed films are not intended for independent use as packaging material but should be applied as part of combined packaging as a protective layer. The scope of application of the current research results is the packaging of food products, namely fruit and vegetable pastes and sauces.